Preparation method of corrosion-resistant coating of aluminum alloy valve

By using weakly alkaline electrolyte system and pulsed laser technology to form a dense γ-Al2O3 crystal phase oxide layer on the surface of aluminum alloy valves, the problem of corrosion of aluminum alloy valves in chloride-rich environments is solved, and efficient corrosion resistance and mechanical strength improvement is achieved.

CN119824406APending Publication Date: 2025-04-15GUANGXI SPECIAL EQUIP SUPERVISION & INSPECTION INST P R CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046076.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Aluminum alloy valves are prone to severe corrosion in chloride-rich environments, which damage structural integrity and increase maintenance costs. The prior art corrosion-resistant coatings lack surface strength and durability in high flow velocity water flow environments.

Method used

The surface modification is performed using a weakly alkaline electrolyte system (sodium hexametaphosphate) combined with pulsed laser. The pulsed laser beam is driven to scan the surface of the aluminum alloy valve back and forth through a two-dimensional moving platform to form a dense γ-Al2O3 crystal phase anti-corrosion oxide layer.

Benefits of technology

It significantly improves the corrosion resistance and mechanical strength of aluminum alloy valves, reduces production costs and energy consumption, and provides coatings with high stability, environmentally friendly and wide applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824406A_ABST
    Figure CN119824406A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a corrosion-resistant coating of an aluminum alloy valve, which is characterized in that surface modification is innovatively carried out by adopting a mode of combining a weakly alkaline electrolyte system (sodium hexametaphosphate) with pulse laser, and a gamma-Al2O3 crystal phase corrosion-resistant oxide layer with a micro-nano structure is controllably prepared on the surfaces of a valve body and a valve clack of the aluminum alloy valve of special equipment. Compared with a common coating prepared by an acidic or strongly alkaline electrolyte system in the prior art, the coating has the characteristics of high stability, environmental friendliness, wide applicability and the like. The alkalescent sodium hexametaphosphate is low in cost and free of pollution. In addition, due to the characteristics of the pulse laser, the preparation process is low in power and small in heat effect, additional cooling equipment is not needed for cooling, a large amount of energy is saved, and the production cost is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material surface modification, and in particular to a method for preparing a corrosion-resistant coating for an aluminum alloy valve. Background Art

[0002] Valves are common components in pipeline systems. Their main function is to control pipeline switches and regulate the flow of fluids in the pipe. Globe valves and butterfly valves are widely used in seawater pipelines because of their good sealing and precise flow control. However, during service, valves will switch between normally open, normally closed, and half-open states according to actual needs. The state change of the valve will cause drastic changes in the flow state of seawater in the valve, increasing the corrosion risk of the valve. At present, the most common valve material is bronze, including tin bronze, aluminum bronze, and nickel aluminum bronze. In actual service, crevice corrosion, erosion corrosion, and cavitation corrosion usually occur. At the same time, high-velocity water will flow through the damaged sealing surface to cause erosion corrosion, leading to further corrosion at the damaged sealing surface. Aluminum alloy materials have broad prospects in the manufacture and use of valve bodies and valve discs because of their low density, high strength, good toughness, and excellent corrosion resistance. However, in chloride-rich environments, such as seawater, aluminum alloys are prone to severe corrosion, which damages structural integrity and significantly increases maintenance costs. Aluminum's native oxide layer offers limited protection due to its inhomogeneous, porous and amorphous structure and is highly susceptible to chloride ion penetration.

[0003] Traditional surface treatment methods, including coating, electroplating, anodizing, plasma electrolytic oxidation (PEO), and micro-arc oxidation (MAO), have been widely studied to mitigate corrosion. However, these methods face challenges such as environmental risks, high energy consumption, or limited durability in harsh environments. Among them, MAO has become a promising method due to its ability to form a dense ceramic oxide layer through high-voltage electrolysis and plasma-assisted processes. Weakly alkaline electrolyte solutions, such as NaSiO 3 , which plays a vital role in this process. These electrolytes not only contribute to the growth of the oxide film and the dissipation of heat, but also participate in the oxidation reaction as an oxygen source to generate an oxide layer, forming a composite ceramic coating, which significantly improves the corrosion resistance and mechanical strength. However, high energy consumption, defect formation caused by thermal stress, and the need for additional cooling equipment limit the industrial-scale application of MAO. At the same time, pulsed lasers that can also provide plasma do not have these disadvantages because of their very small thermal effects.

[0004] Pulse laser technology has attracted more and more attention due to its precision, energy concentration and environmental friendliness. When applied to aluminum alloys, pulse laser can clean surface contaminants, refine grains and generate a dense oxide layer, thereby enhancing corrosion resistance. In a certain literature, high-speed laser cladding and strengthening materials such as Y 2 O 3When used in combination, it has been shown that dense coatings with refined grains and enhanced mechanical properties and corrosion resistance can be produced. Techniques such as laser shock processing (LSP) and laser powder bed fusion (LPBF) have also been shown in a certain literature to significantly improve the mechanical properties of metal alloys, including strength and corrosion resistance. Similarly, selective laser melting (SLM) in a certain literature is able to produce fine-grained structures and low porosity, providing excellent corrosion resistance and biomedical properties. Pulsed laser technology, including nanosecond, picosecond and femtosecond lasers, can provide a certain degree of corrosion resistance in addition to laser cleaning. A study used pulsed lasers to clean cultural relics, which not only protected the integrity of the cultural relics themselves, but also provided a certain degree of corrosion resistance, thereby preventing further deterioration. In addition, there are studies that use pulsed lasers to combine ultrafast ablation with chemical oxidation to create micro / nano structures with excellent wettability and durability, promoting the manufacture of superhydrophobic surfaces. On the basis of this superhydrophobic surface, a certain literature pointed out that the introduction of hydrophobic groups through subsequent chemical modification can further enhance surface wettability and reduce corrosion rates. A study demonstrated that laser-induced technology can simplify the fabrication of superhydrophobic graphene. The rapid heating and cooling cycles of the pulsed laser form a high-temperature, high-pressure interface, driving plasma-assisted reactions that modify the surface and crystal structure, ultimately improving the material's properties.

[0005] The corrosion-resistant coating manufactured by laser additive manufacturing in the existing technology requires a large amount of energy input and expensive reinforcement materials. The corrosion-resistant coating of aluminum alloy valves provides insufficient corrosion resistance in chlorine-rich environments. The surface of the corrosion-resistant coating of aluminum alloy valves often lacks strength and durability, which limits their anti-corrosion capabilities.

[0006] Therefore, there is an urgent need to develop a method for preparing a corrosion-resistant coating for aluminum alloy valves. Summary of the invention

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] A method for preparing a corrosion-resistant coating for an aluminum alloy valve comprises the following steps:

[0009] (1) preparing a sodium hexametaphosphate solution, wherein the concentration of the sodium hexametaphosphate solution is 8 to 10 g / L; preparing a hydrogen peroxide solution, wherein the concentration of the hydrogen peroxide solution is 2 to 5 g / L; and mixing the sodium hexametaphosphate solution and the hydrogen peroxide solution to obtain a prepared solution;

[0010] (2) Grinding the surface of the aluminum alloy valve to be coated;

[0011] (3) Immerse the aluminum alloy valve in the prepared solution so that the liquid surface covers the upper surface of the aluminum alloy valve by 1-3 mm;

[0012] (4) Adjust the parameters of the pulse laser beam modulation device, and use the two-dimensional mobile platform to drive the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy valve 26-30 times;

[0013] (5) After scanning, the aluminum alloy valve is cooled in the prepared solution for 1-2 hours, ultrasonically cleaned with methanol for 5-10 minutes, and dried at room temperature for 24-30 hours to form a corrosion-resistant coating on the surface of the aluminum alloy valve.

[0014] Preferably, in step (2), the surface of the aluminum alloy valve is polished with sandpaper having a particle size of 240#, 500#, and 800#, respectively.

[0015] Preferably, the concentration of the sodium hexametaphosphate solution in the prepared solution in step (1) is 10 g / L. Too high a concentration will increase the corrosion current density, while too low a concentration will cause the surface γ-Al 2 O 3 The crystalline content is reduced.

[0016] Preferably, the concentration of hydrogen peroxide in the prepared solution in step (1) is 2.5 g / L.

[0017] Preferably, the solution prepared in step (3) covers the upper surface of the aluminum alloy valve by 3 mm.

[0018] Preferably, in step (4), the pulse laser beam modulation device has a power of 70-90 W, a pulse frequency of 510-520 kHz, and a pulse width of 170-190 ns.

[0019] Furthermore, the optimal focal length of the pulse laser beam modulation device is 23.5 cm.

[0020] Furthermore, in step (4), the pulse laser beam modulation device has a power of 90 W, a pulse frequency of 510 kHz, and a pulse width of 170 ns.

[0021] Furthermore, in step (4), the two-dimensional mobile platform scans back and forth 30 times.

[0022] Furthermore, in the step (5), the aluminum alloy valve is cooled in the prepared solution for 1 hour, ultrasonically cleaned with methanol for 5 minutes, and then taken out and dried at room temperature for 24 hours.

[0023] Due to the adoption of the above technical solution, the present invention has the following technical advances compared with the prior art:

[0024] 1) This application innovatively uses a weak alkaline electrolyte system (sodium hexametaphosphate) combined with a pulsed laser to perform surface modification, and can controllably prepare γ-Al with micro-nano structure on the surface of the valve body and valve disc of special equipment aluminum alloy valves. 2 O 3Compared with the coatings prepared by the acidic or strongly alkaline electrolyte systems commonly used in the prior art, this coating has the characteristics of high stability, environmental friendliness and wide applicability.

[0025] 2) Weakly alkaline sodium hexametaphosphate, low cost and pollution-free. In addition, due to the characteristics of the pulsed laser itself, the preparation process has low power, small thermal effect and no need for additional cooling equipment, which saves a lot of energy and significantly reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0027] Figure 1 These are the surface micromorphologies of samples AA0, AA1, and AA2 under the secondary electron mode of a scanning electron microscope.

[0028] Figure 2 These are the electrochemical corrosion test results of three samples: AA0, AA1, and AA2. DETAILED DESCRIPTION

[0029] The following embodiments may help those skilled in the art to more fully understand the present invention, but shall not limit the present invention in any way.

[0030] Example

[0031] A method for preparing a corrosion-resistant coating for an aluminum alloy valve comprises the following steps:

[0032] (1) preparing a sodium hexametaphosphate solution, wherein the concentration of the sodium hexametaphosphate solution is 8 to 10 g / L; preparing a hydrogen peroxide solution, wherein the concentration of the hydrogen peroxide solution is 2 to 5 g / L; and mixing the sodium hexametaphosphate solution and the hydrogen peroxide solution to obtain a prepared solution;

[0033] (2) Grinding the surface of the aluminum alloy valve to be coated;

[0034] (3) Immerse the aluminum alloy valve in the prepared solution so that the liquid surface covers the upper surface of the aluminum alloy valve by 1-3 mm;

[0035] (4) Adjust the parameters of the pulse laser beam modulation device, and use the two-dimensional mobile platform to drive the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy valve 26-30 times;

[0036] (5) After scanning, the aluminum alloy valve is cooled in the prepared solution for 1-2 hours, ultrasonically cleaned with methanol for 5-10 minutes, and dried at room temperature for 24-30 hours to form a corrosion-resistant coating on the surface of the aluminum alloy valve.

[0037] In one embodiment of the present invention, in step (2), the surface of the aluminum alloy valve is polished using sandpaper with particle sizes of 240#, 500#, and 800#, respectively.

[0038] In one embodiment of the present invention, the concentration of the sodium hexametaphosphate solution in the prepared solution in step (1) is 10 g / L. Too high a concentration will increase the corrosion current density, while too low a concentration will cause the surface γ-Al 2 O 3 The crystalline content is reduced.

[0039] In one embodiment of the present invention, the concentration of hydrogen peroxide in the prepared solution in step (1) is 2.5 g / L.

[0040] In one embodiment of the present invention, the solution prepared in step (3) covers the upper surface of the aluminum alloy valve by 3 mm.

[0041] In one embodiment of the present invention, in step (4), the power of the pulse laser beam modulation device is 70-90 W, the pulse frequency is 510-520 kHz, and the pulse width is 170-190 ns.

[0042] Furthermore, the optimal focal length of the pulse laser beam modulation device is 23.5 cm.

[0043] Furthermore, in step (4), the pulse laser beam modulation device has a power of 90 W, a pulse frequency of 510 kHz, and a pulse width of 170 ns.

[0044] Furthermore, in step (4), the two-dimensional mobile platform scans back and forth 30 times.

[0045] Furthermore, in the step (5), the aluminum alloy valve is cooled in the prepared solution for 1 hour, ultrasonically cleaned with methanol for 5 minutes, and then taken out and dried at room temperature for 24 hours.

[0046] Experimental example

[0047] (1) Cut the valve disc of the aluminum alloy valve or the aluminum alloy metal block to obtain three identical aluminum alloy blocks, and grind them with sandpaper of 240#, 500#, and 800# grits in turn for use;

[0048] (2) Number the three aluminum alloy blocks respectively as AA0, AA1, and AA2.

[0049] (3) The prepared solution was submerged 3 mm above the upper surface of AA1, the parameters of the pulse laser beam modulation device were adjusted, and the height of the pulse laser output device was adjusted to the optimal focal length. The pulse laser beam modulation device was driven by a two-dimensional mobile platform to scan back and forth on the surface of AA1 30 times, and the scanning speed was 100 mm / min; the power of the pulse laser beam modulation device was 90 W, the pulse frequency was 510 kHz, and the pulse width was 170 ns. After the scanning was completed, it was cooled in the prepared solution for 1 h, ultrasonically cleaned with methanol for 5 min, and taken out and dried at room temperature for 24 h.

[0050] (4) Directly use a pulse laser beam modulation device driven by a two-dimensional mobile platform to scan back and forth on the surface of AA2 30 times, with a scanning speed of 100 mm / min; the pulse laser beam modulation device has a power of 90 W, a pulse frequency of 510 kHz, and a pulse width of 170 ns. After scanning, cool and dry in air for 25 hours.

[0051] The surface oxide layer microstructure of AA0, AA1 and AA2 was analyzed in turn. The results can be seen in Figure 1 ,pass Figure 1 It can be concluded that a uniform and dense oxide layer is obviously formed on the surface of the AA1 sample treated by the prepared solution combined with the pulsed laser induced plasma effect, which significantly reduces the surface porosity and further optimizes the surface microstructure of the aluminum alloy. Compared with the AA2 sample that is directly treated with pulsed laser without using a solution system, the oxide layer on the surface of the AA1 sample is denser and the pores are significantly reduced, which helps to improve the ability of the aluminum alloy valve body and valve disc to resist crevice corrosion, erosion corrosion and cavitation corrosion.

[0052] At the same time, electrochemical corrosion tests were carried out on AA0, AA1, and AA2. The results can be found in Figure 2 ,pass Figure 2 It can be concluded that the AA1 sample treated with sodium hexametaphosphate solution combined with pulsed laser induced plasma effect exhibits better corrosion resistance. According to the Tafel extrapolation method, the corrosion current density of the AA1 sample is one order of magnitude lower than that of the AA2 sample, and the corrosion potential is positively shifted by about 0.03V, indicating that its oxide layer has higher density and stronger dielectric barrier ability. The positive shift of the corrosion potential indicates that the coating can effectively inhibit the penetration of corrosive media, and the significant reduction in the corrosion current density further verifies that the oxide layer can quickly form a dense protective film or passivation layer in a corrosive environment, thereby significantly improving the corrosion resistance. Therefore, compared with the AA2 sample directly laser-treated, the oxide layer of the AA1 sample assisted by sodium hexametaphosphate solution has better anti-corrosion performance and is suitable for application scenarios exposed to corrosive environments for a long time.

[0053] The above generally describes the present invention in detail, but it is obvious to a person skilled in the art that some modifications or improvements can be made to the present invention. Therefore, modifications or improvements that do not depart from the spirit of the present invention are within the scope of protection of the present invention.

Claims

1. A method for preparing a corrosion-resistant coating for an aluminum alloy valve, characterized in that: The following steps are involved: (1) preparing a sodium hexametaphosphate solution, wherein the concentration of the sodium hexametaphosphate solution is 8 to 10 g / L; preparing a hydrogen peroxide solution, wherein the concentration of the hydrogen peroxide solution is 2 to 5 g / L; and mixing the sodium hexametaphosphate solution and the hydrogen peroxide solution to obtain a prepared solution; (2) Grinding the surface of the aluminum alloy valve to be coated; (3) Immerse the aluminum alloy valve in the prepared solution so that the liquid surface covers the upper surface of the aluminum alloy valve by 1-3 mm; (4) Adjust the parameters of the pulse laser beam modulation device, and use the two-dimensional mobile platform to drive the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy valve 26-30 times; (5) After scanning, the aluminum alloy valve is cooled in the prepared solution for 1-2 hours, ultrasonically cleaned with methanol for 5-10 minutes, and dried at room temperature for 24-30 hours to form a corrosion-resistant coating on the surface of the aluminum alloy valve.

2. The method for preparing the corrosion-resistant coating of aluminum alloy valves according to claim 1, characterized in that: In step (2), the surface of the aluminum alloy valve is polished with sandpapers of 240#, 500#, and 800# grits in sequence.

3. The method for preparing the corrosion-resistant coating of aluminum alloy valves according to claim 1, characterized in that: The concentration of the sodium hexametaphosphate solution in the prepared solution of step (1) is 10 g / L; the concentration of hydrogen peroxide in the prepared solution of step (1) is 2.5 g / L.

4. The method for preparing the corrosion-resistant coating of aluminum alloy valves according to claim 1, characterized in that: In step (4), the power of the pulse laser beam modulation device is 70-90W, the pulse frequency is 510-520kHz, and the pulse width is 170-190ns.

5. The method for preparing the corrosion-resistant coating of aluminum alloy valves according to claim 1, characterized in that: The optimal focal length of the pulse laser beam modulation device is 23.5cm.

6. The method for preparing the corrosion-resistant coating of aluminum alloy valves according to claim 4, characterized in that: In step (4), the pulse laser beam modulation device has a power of 90 W, a pulse frequency of 510 kHz, and a pulse width of 170 ns.

7. The method for preparing the corrosion-resistant coating of aluminum alloy valves according to claim 1, characterized in that: In step (4), the two-dimensional mobile platform scans back and forth 30 times.

8. The method for preparing the corrosion-resistant coating of aluminum alloy valves according to claim 1, characterized in that: In step (5), the aluminum alloy valve is cooled in the prepared solution for 1 hour, ultrasonically cleaned with methanol for 5 minutes, and then taken out and dried at room temperature for 24 hours.

9. The method for preparing the corrosion-resistant coating of aluminum alloy valves according to claim 1, characterized in that: Step (3) The prepared solution covers the upper surface of the aluminum alloy valve by 3 mm.